Effectiveness of Mindfulness Therapy on Anxiety among Elderly Residents at Panti Sosial Tresna Werdha Natar - Anisa Fitri; Sujiah Sujiah; Miranti Dea Dora (Inspirasi Foundation, 2027)
Objective: Older adults are more likely to experience anxiety disorders than depression. Common psychosocial problems in this population include loneliness, sadness, depression, and anxiety. Anxiety among older adults is often associated with fear of death, loss of independence, and feelings of abandonment after relocation to residential care facilities. This study aimed to determine the effect of mindfulness therapy on anxiety levels among older adults living in a residential care home. Methods: This quantitative study employed a pre-experimental design using a one-group pretest–posttest approach. A total of 38 older adults with anxiety were recruited through purposive sampling from a residential care home in South Lampung, Indonesia. Anxiety levels were measured before and after the intervention, and the data were analyzed using a paired-samples t-test. Results: The mean anxiety score decreased from 21.05 before the intervention to 16.39 after mindfulness therapy. The paired-samples t-test showed a statistically significant reduction in anxiety levels (p < 0.001), indicating that mindfulness therapy effectively reduced anxiety among older adults. Conclusion: Mindfulness therapy significantly reduced anxiety levels among older adults living in a residential care home. These findings suggest that mindfulness therapy can be considered an effective non-pharmacological nursing intervention for managing anxiety in older adults.